Strategi Manajemen Kurikulum Dan Pembelajaran Bahasa Indonesia Dalam Upaya Peningkatan Kualitas Pendidikan - M. Rudi Gunawan P; Fadma Rosita (Peneliti.net, 2023)
The purpose of this study is to analyze the curriculum management strategy implemented by the Yogyakarta Pangudi Luhur school. Knowing the suitability of curriculum development with the Indonesian language learning process. then draw conclusions and decide on the policy to be implemented. This research method is a descriptive case study method. This research was conducted at Kanisius Pangudi Luhur Middle School, Yogyakarta. The research was conducted in January 2021. Data sources from this research were participants, informants, informants, and teachers. Data collection techniques in descriptive case study research are documents, archival records, interviews, direct observation, participant observation, and physical devices. The data analysis technique used in analyzing the problem formulation is an interactive technique. The results of the research that has been carried out are as follows: PL schools have implemented competency-based curriculum management, which is carried out in the following steps: 1) School Program Planning and Evaluation; 2) Competency-Based Curriculum Development; 3) Learning Development; 4) Manpower Management; 5) Management of Learning Facilities and Resources; 6) Financial Management; 7) Student Services; 8) School and Community Relations; and 9) Creating a School Climate. Schools also carry out curriculum development using the principles of Relevance, Flexibility, Continuity, Efficiency, and Effectiveness which enable schools to carry out learning more in schools by using the right stages and application to students. The Indonesian language learning curriculum in schools uses the Text-based K13 curriculum, which consists of 4 stages, namely 1) the context-building stage, 2) the text modeling stage, 3) the text-making stage together, and 4) the text-making stage independently With words On the other hand, the school has fulfilled the curriculum management criteria and the management of the Indonesian language learning curriculum very well. teachers and principals have worked together in carrying out curriculum management by carrying out curriculum development. There needs to be an improvement in the media used, namely the need to improve learning media that is more environmentally friendly, natural, and efficient. Students can take an active part in developing the curriculum by creating learning media independently.